Feedbasic : a guide to implement feedback practices for remote software development teams - RIBEIRO, Ana Beatriz Cavalcanti (2023)
Feedback is an essential part of the routine of software development teams. Different feedback practices have been adopted by leaders and managers to provide information on employee performance, align goals and resolve conflicts. The significant growth in the adoption of the remote work model has created new challenges to the effective and sustainable use of feedback by organizations. The main challenges include lack of trust within the team, loss of access to body language and limited access to information regarding the performance of the collaborator. Despite the recognized importance of feedback in motivating employees and the challenge of performing it in the context of remote work, there is a lack of studies focused on understanding how feedback practices are currently conducted in remote software development teams. From this context, the objective of this work is to explore how feedback practices are being conducted by software development teams that work totally or partially in remote model. For this, a mixed research method was used to capture the different perspectives associated with feedback practices. We performed a multivocal literature review to map the benefits, limitations, and good practices of feedback. Then, we conducted semi-structured interviews with 10 leaders and managers of software development teams to understand their perceptions about feedback practices. Finally, we surveyed 83 members of several remote software teams to get their perceptions and feelings about receiving feedback. The triangulation of data collected from different research methods enabled the development of FeedBasic, a guide aimed at implementing and improving feedback in remote software development teams to improve employees’ satisfaction and effectiveness of the feedback process. Among the good practices proposed by the FeedBasic include the development of an action plan focused on the evolution of the employee, and the frequent monitoring of their progress towards the established goals. These practices may boost team engagement and make the process more enriching for the collaborator.